Developing Germplasm and Promoting Consumption of Anthocyanin-Rich Grains for Health Benefits - Dwivedi, Sangam L.; Mattoo, Autar K.; Garg, Monika; Dutt, Som; Singh, Brajesh; Ortiz, Rodomiro (Frontiers in Sustainable Food Systems, 2022)
Malnutrition, unhealthy diets, and lifestyle changes are the major risk factors for overweight and obesity-linked chronic diseases in humans adversely impact achieving sustainable development goals. Colored grains are a source of anthocyanins, a group of flavonoids, that contribute positively to human health. This review focuses on genetic variation harnessed through breeding and biotechnology tools for developing anthocyanin-rich grain crops. Agronomic practices, genotype × environment interactions, different stresses, seed development and seed maturity are factors that impact the content and composition of anthocyanins. Significant progress has been made in characterizing genes associated with anthocyanin biosynthesis in cereal and other crops. Breeding has led to the development and release of grain anthocyanin-rich crop cultivars in Europe, America and in some countries in Asia. Notably, genetic engineering utilizing specific transcription factors and gene editing has led to the development of anthocyanin-rich genetic variants without any significant yield penalty. A variety of food products derived from colored grains or flours are now available in grocery stores and supermarkets worldwide. The public perception about anthocyanin-rich food is positive, but availability, affordability, and willingness to pay a higher price than before limit consumption. Together with other seed nutrition traits in breeding programs the inclusion of anthocyanins can ensure the development of cultivars that meet nutrition needs of humans, especially in the developing world.